The Effectiveness of Virtual Leadership Requirements in Saudi Universities Considering the Indicators of the National Center for E-Learning - Dr. Sylvia Ismail Mohammad Bani Hani (Journal of Educational and Human Sciences, 2022)
The study sought to determine the effectiveness of virtual leadership requirements in Saudi universities in light of the indicators of the National Center for E-Learning. The questionnaire was adopted in this research and was given to a sample of 33 faculty members at the University of Hail. The study used a descriptive analytical technique. The research came to the conclusion that the mathematical mean of the three study dimensions—ideal influence, inspirational motivation, and empowerment—had a high level of effectiveness and within a range of 68% to 84%.The results also showed the absence of obstacles, as the arithmetic mean of the field of obstacles was (2.42), which is in a weak degree. Through the results, it was found in the study procedures that there is an effectiveness of the requirements of virtual leadership at the University of Hail in the light of the indicators of the National Center for E-Learning.